Ki67 expression at Kasai portoenterostomy as a prognostic factor in patients with biliary atresia. Issue 5 (16th June 2020) - Yoshii, D; Inomata, Y; Komohara, Y; Shimata, K; Honda, M; Hayashida, S; Oya, Y; Yamamoto, H; Yamamoto, H; Sugawara, Y; Hibi, T
Abstract: Background: Biliary atresia is a rare paediatric biliary obliteration disease with unknown aetiology, and is the most common indication for paediatric liver transplantation (LT). However, no consensus for predicting Kasai portoenterostomy (KP) outcomes using liver histological findings exists. Ki67 is a popular biomarker for measuring and monitoring cellular proliferation. Methods: Ki67 (clone, MIB-1) liver parenchyma expression was measured by immunohistochemical staining of samples from living donors and patients with biliary atresia to assess its value in predicting outcomes after KP. Results: Of 35 children with biliary atresia, 13 were native liver survivors (NLS), 17 were non-NLS, and five had primary LT. The median proportion of Ki67 immunostained areas in donors and patients with biliary atresia at KP was 0·06 and 0·99 per cent respectively. Univariable analysis identified a high proportion of Ki67 areas, high Ki67 cell numbers and high Ki67-positive/leucocyte common antigen-positive cell numbers at KP as significant predictors of poor native liver survival after KP (hazard ratio 9·29, 3·37 and 12·17 respectively). The proportion of Ki67 areas in the non-NLS group was significantly higher than that in the NLS group (1·29 versus 0·72 per cent respectively; P  = 0·001), and then decreased at LT (0·32 per cent versus 1·29 per cent at KP; P < 0·001). Conclusion: This study has demonstrated the clinical data and time course of Ki67 expression in patients with biliary atresia. High Ki67 expression at KP may be an important predictor of native liver survival following the procedure. Graphical Abstract: No consensus exists for predicting outcomes after Kasai portoenterostomy (KP) using liver histological findings. Ki67 (clone, MIB-1) expression in liver parenchyma was measured by means of immunohistochemical staining of samples from five living donors and 35 patients with biliary atresia to assess its value in predicting KP outcomes. Univariable analysis identified high expression of Ki67 at the time of KP as a significant predictor of poor native liver survival after the procedure. Ki67 a potential marker for liver survival after Kasai portoenterostomy